Thematic Classification of Eshqabil Shukur's Poetry - Ergashova Sadokat Eshmamat kizi (Journal of Learning on History and Social Sciences, 2024)
This article reveals the thematic classification of the poetry of the talented poet Eshqabil Shukur. In the course of the article, the unique and colorful themes of the poet's poems are analyzed. At the end of the article there is a conclusion and a comment.